2007
DOI: 10.1097/mpg.0b013e318054b0dd
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practice Styles of North American Pediatricians Regarding Gastroesophageal Reflux Disease

Abstract: Pediatric providers appear to frequently order diagnostic testing and treatment for GERD, yet knowledge about evidence-based GERD management among this random sample appeared limited. Moreover, a significant number of providers were not aware of different guideline publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 29 publications
4
43
1
3
Order By: Relevance
“…A recent survey of members of the American Academy of Pediatrics found a wide variety of professional opinions with regard to the diagnosis and management of GERD and reported that the awareness of evidence-based practices for GERD was lacking among practitioners [8]. Although guidelines for the evaluation and management of GERD exist, there is little evidence to support that such recommendations are being followed with any consistency [9].…”
Section: Discussionmentioning
confidence: 98%
“…A recent survey of members of the American Academy of Pediatrics found a wide variety of professional opinions with regard to the diagnosis and management of GERD and reported that the awareness of evidence-based practices for GERD was lacking among practitioners [8]. Although guidelines for the evaluation and management of GERD exist, there is little evidence to support that such recommendations are being followed with any consistency [9].…”
Section: Discussionmentioning
confidence: 98%
“…Such comparison has been discussed in the literatures. [23] In conclusion, GERS has been validated as a tool for the evaluation of patients with suspected GER. VI is better than the CI and TAC methods in terms of accuracy and inter-observer reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…A less ambiguous option is, "In what state do you practice pediatric general surgery?" Questions written with a clear focus will yield responses that are informative, accurate, and reliable [11]. Questionnaire items should limit the outside information participants must rely on to give an accurate response [12].…”
Section: Preliminary Question Designmentioning
confidence: 99%